JALAN TERJAL IMPLEMENTASI PERUBAHAN TARIF PAJAK UMKM - Donna Friska; I Gede Sanica (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to find out and analyze the application of PP No. 23 of 2018 to MSME WP tax compliance and the strategy carried out by KPP Pratama Soreang to increase MSME taxpayer compliance. The design of this study uses descriptive qualitative as well as quantitative methods. The data collection was carried out through documentation studies and interviews with KPP Soreang officials and MSME taxpayers. The results of the study show some information, namely 1) the application of PP No 23 of 2018 at KPP Pratama Soreang to increase taxpayer compliance has been successful, indicated by an increase in the number of MSME taxpayers, 2) The MSME business community positively welcomes the reduction in the final tax rate for MSMEs from 1% to 0.5%, 3) Tax revenue at KPP Pratama Soreang has decreased in 2018 and 2019 because the additional amount of MSME mandatory tax has not been in line with the magnitude of the decrease due to reduced rates. 4) KPP Pratama Soreang implements a strategy to increase taxpayers and revenue through massive outreach by inviting taxpayers to the office, direct visits to taxpayer locations (door to door)